2005
DOI: 10.1093/jac/dki430
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in the brains of rabbits experimentally infected with Angiostrongylus cantonensis after albendazole treatment: histopathological and magnetic resonance imaging studies

Abstract: Pathological changes in the brains of the treated rabbits are more severe than those without albendazole treatment, suggesting that the drug may not be very suitable for the treatment of cerebral angiostrongyliasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The major pathological damages in human CNS induced by A. cantonensis infection include; (1) meningitis with a predominance of eosinophils and plasma cells; (2) multiple microcavities, tortuous tracks, and microscopic hemorrhage surrounded by inflammatory cells and neuron lesions in the brain and spinal cord parenchyma; (3) granulomatous response to the dead worms; (4) nonspecific vascular reactions, thrombosis, and aneurysm formation [ 42 , 44 ]. In A. cantonensis -infected mammalian brains (permissive host rats and nonpermissive hosts, including mice, rabbits, and guinea pigs), similar pathological changes were also found in CNS [ 23 , 24 , 28 , 29 , 45 , 46 ]. In this study, plaque-like lesions also showed in various regions in infected animals.…”
Section: Discussionmentioning
confidence: 87%
“…The major pathological damages in human CNS induced by A. cantonensis infection include; (1) meningitis with a predominance of eosinophils and plasma cells; (2) multiple microcavities, tortuous tracks, and microscopic hemorrhage surrounded by inflammatory cells and neuron lesions in the brain and spinal cord parenchyma; (3) granulomatous response to the dead worms; (4) nonspecific vascular reactions, thrombosis, and aneurysm formation [ 42 , 44 ]. In A. cantonensis -infected mammalian brains (permissive host rats and nonpermissive hosts, including mice, rabbits, and guinea pigs), similar pathological changes were also found in CNS [ 23 , 24 , 28 , 29 , 45 , 46 ]. In this study, plaque-like lesions also showed in various regions in infected animals.…”
Section: Discussionmentioning
confidence: 87%
“…Several dogs in the historical cohort worsened despite treatment with glucocorticoids, possibly due to this phenomenon. Clearly, mechanical damage due to migrating larvae and inflammation secondary to the appropriate host immune response both contribute to neural damage [43,66,81-85]. Which of the two is the more significant depends on (i) the age, species and breed of the infected host, (ii) the number of larvae ingested and the time course over which infection occurs, (iii) the physical dimensions of the spinal cord and nerve roots.…”
Section: Discussionmentioning
confidence: 99%
“…Both experimental infection studies and isolated reports indicate that killing the worms may exacerbate inflammation and increase the severity of the disease (164,291). Prednisolone (60 mg/kg of body weight/day for 2 weeks) and albendazole (15 mg/kg twice a day [b.i.d.]…”
Section: Treatmentmentioning
confidence: 99%